Minuman Fungsional Dari Kombinasi Kopi Hijau Robusta (Coffea canephora), Ekstrak Gambir (Uncaria gambir Roxb.) dan Pasak Bumi (Eurycoma longifolia Jack) - Diatari Agustini; Syerina Raihatul Jannah; Agus Wijaya (Jurnal BETAHPA, 2022)
The objective of this research was to design beverage product with functional properties from the combination of green coffee Robusta, gambir extract and pasak bumi. The research used a Non-factorial Completely Randomized Design (CRD) consisting of 5 levels to obtain 5 treatments. Each treatment was repeated 3 (three) times. The parameters observed in this study included physical characteristics (solubility), chemistry (pH, total phenol and antioxidant activity), and microbiology (antibacterial activity). The results showed that the formulation of green coffee Robusta, gambir extract and pasak bumi had significant effect on solubility, pH, total phenol, and antioxidant activity. Characteristic of functional drink was produced pH 5.08 to 5.24, solubility 8.28 to 34.7%, total phenol 26.29 to 119.67 mg/g, antioxidant activity (IC50) 40.97 to 62.13 ppm, and clear zone diameter formed in Staphylococcus aureus reaches ±5 mm for gambir (control treatment). Based on antioxidant activity and total phenol, the best treatment was F5 (green coffee 60% : gambir 30% and pasak bumi 10%).